New Legal Standards for Investment Policy of Open Pension Funds - Jakubowski, Sebastian (Economic and Environmental Studies, 2020)
The global financial crisis affected also Polish pension market. Low or negative rate return on pension capital accumulated in Open Pension Funds led to social disappointment and growth of feeling of social insecurity. Prolonged financial crisis together with sluggish economic growth forced first reform of Open Pension Funds system in 2011. Second reform was introduced just three years later. On February 3rd Open Pension Funds were forced to transfer 51,5% of their assets to Social Security Institution. The total value of transferred cash and fixed income assets was 153 151,2 mln PLN. The transfer left Open Pension Funds mainly with equity allocations and fundamentally changed their investment policy. From domestic stable growth funds OFE had to change to equity funds. Together with the transfer of half of OFE capital major legal changes were introduced liberalizing investment policy of Open Pension Funds in the long term. The goal of this study is to analyze the legal changes of investment standards that shape the investment policy of Open Pension Funds today. Evolution of investment standards for Open Pension Funds during last fifteen years is analyzed with special emphasis on the consequences of the transfer of Open Pension Funds’ capital to Social Security Institution.